Pengaruh Social Media Marketing, Fear of Missing Out, dan Hedonic Motivation terhadap Impulsive Buying pada Eiger Store - Delsy Andira; Lilik Indayani; Misti Hariasih (Universitas Batanghari Jambi, 2026)
This study aims to analyze the influence of Social Media Marketing, Fear of Missing Out (FOMO), and Hedonic Motivation on Impulsive Buying among Eiger Store consumers. The study used a quantitative approach with a survey method of 100 Eiger Store consumer respondents in East Java Province aged 19-35 years and had purchased Eiger products at least once. The sampling technique used purposive sampling. Data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The results showed that Social Media Marketing, Fear of Missing Out (FOMO), and Hedonic Motivation had a positive and significant effect on Impulsive Buying. This study provides practical implications for Eiger Store to optimize digital marketing strategies by considering the psychological aspects and hedonic motivations of consumers, especially Generation Z, in increasing sales effectiveness.